The evaluation of swallowing in patients with spinocerebellar ataxia and oropharyngeal dysphagia: A comparison study of videofluoroscopic and sonar doppler - Abdulmassih, Edna Márcia da Silva; Teive, Hélio Afonso Ghizoni; Santos, Rosane Sampaio (International Archives of Otorhinolaryngology, 2013)
Introduction: Spinocerebellar ataxia (SCA) is a degenerative disease that can cause loss of coordination of voluntary muscle movement such as that required for swallowing.Aims: The purposes of this cross-sectional and comparative case study were: (1) to assess the severity of dysphagia through a videofluoroscopic swallow study, and (2) to compare differences in frequency, intensity, and duration of sound waves produced during swallowing in normal and SCA patients by using sonar Doppler.Method: During swallow evaluation using videofluoroscopy, a sonar Doppler transducer was placed on the right side of the neck, at the lateral edge of the trachea, just below the cricoid cartilage to capture the sounds of swallowing in 30 SCA patients and 30 controls.Result: The prevalence in the dynamic evaluation of swallowing videofluoroscopy was by changes in the oral phase of swallowing. The analysis of variance of the averages found in each variable - frequency, intensity and duration of swallowing - shows there was a significant correlation when compared to the healthy individual curve.Conclusion: The study demonstrates the prevalence of oral dysphagia observed in dynamic videofluoroscopic swallow evaluation. In patients with SCA, the mean initial frequency (IF), initial intensity (II), and final intensity (FI) were higher and the time (T) and peak frequency (PF) were lower, demonstrating a pattern of cricopharyngeal opening very close to that found in normal populations.
Keywords: Deglutition Disorders; Spinocerebellar Ataxias; Doppler Effect